Factors Associated with the Incidence of Anemia among Adolescent Girls at SMK Bina Sriwijaya Indonesia, Palembang City, 2026 - Wanda Miliya Apriliani; Sendy Pratiwi Rahmadhani; Rini Gustina Sari; Arie Anggraini (Darul Yasin Al Sys, 2026)
Anemia among adolescent girls remains an important public health concern because it may impair learning concentration and productivity and adversely affect future reproductive health. Dietary practices, adherence to iron–folic acid (IFA) supplementation, and menstrual cycle patterns are among the factors potentially associated with anemia in this population. This study aims to examine the relationships between fast food consumption, adherence to IFA supplementation, menstrual cycle patterns, and anemia among adolescent girls at SMK Bina Sriwijaya Indonesia, Palembang, in 2026. An analytical survey with a cross-sectional design was conducted among a population of 108 adolescent girls, from whom 52 respondents were selected using stratified random sampling. Data were analyzed using the chi-square test at a significance level of α = .05. The findings showed that 28 respondents (53.8%) had anemia, 26 (50.0%) frequently consumed fast food, 31 (59.6%) were non-adherent to IFA supplementation, and 27 (51.9%) had abnormal menstrual cycles. Bivariate analysis demonstrated significant associations between fast food consumption and anemia (p < .001), adherence to IFA supplementation and anemia (p < .001), and menstrual cycle patterns and anemia (p < .001). These findings indicate that dietary behavior, adherence to IFA supplementation, and menstrual health are significantly associated with anemia among adolescent girls. The study contributes empirical evidence supporting integrated anemia-prevention strategies that emphasize balanced dietary practices, reduced fast food consumption, adherence to IFA supplementation, and appropriate monitoring of menstrual health among adolescent girls.